PENGARUH EXPERIENTIAL MARKETING TERHADAP KEPUASAN DAN LOYALITAS PASIEN - shofi nur rahmah (LPPMK STIKES Widyagama Husada, 2021)
This study aimed to examine the effect of experiential marketing on patient satisfaction and patient loyalty. It also attempted to discover the experiential-marketing dimension with the predominant effect. It is a quantitative study with a cross-sectional approach. The study population was all inpatients in Rumah Sakit Islam (RSI) Unisma Malang between February and March 2017. The researchers selected 197 respondents as samples using the purposive sampling method from all ward classes except VVIP class. This study’s exogenous variable was experiential marketing, whereas the endogenous variable was patient satisfaction and loyalty. As the instrument, the researchers used a questionnaire to reveal the patients’ perceptions and hopes about experiential marketing applied by the hospital and their satisfaction and loyalty. The researchers used Partial Least Square (PLS) as a data analysis method. The study showed that experiential marketing dimensions (consisting of sense, feel, think, act, and relate) positively and significantly affected patient satisfaction. Experiential marketing insignificantly and indirectly affected patient loyalty through patient satisfaction, and ‘relate’ was the most dominant dimension of experiential marketing in building patient satisfaction. Keywords: experiential marketing; patient satisfaction; patient loyalty.